PENERAPAN DIVERSI TERHADAP TINDAK PIDANA ANAK DALAM SISTEM PERADILAN PIDANA ANAK - Teguh Prasetyo (Universitas Kristen Satya Wacana, 2015)
AbstractThis article discusses the application of the crime diversion to children in juvenile criminal justice system. So far in the criminal justice system, punishment for perpetrators of children not create justice the perpertrators and victims. On the other hand also still leaves another problem that was not solved even though the perpetrators have been punished. See the principle of the protection of children especially the principle that the best interest of the child. The cild process is required for settling disputes outside the criminal mecanism or commonly referred to as diversion. Settlement through this diversion is expected to provide a win-win solution tho the cases encountered so as to create fairness both in terms of perpertrators as well as for the victim.AbstractThis article discusses the application of diversion in juvenile criminal justice system. So far in the criminal justice system, punishment of juvenile perpetrators of crimes did not create justice for the perpertrators and victims. On the other hand, the system also leaves another problem that has not been solved eventhough the perpetrators have been unished. Noting one of the principles in the protection of children, which is the best interests of the child, criminal cases with children as perpetrators should be settled outside the criminal mechanism generally referred to as diversion. Settlement by way of diversion is expected to create a solution that is balanced so as to create justice for both perpetrators and victims. Nevertheless, the diversion can not be applied to all of the criminal act. Diversion can only be applied in offenses committed by children which are sanctioned by penalty of no more than seven years imprisonment and the offence is not a repetition of crime (recidive).